Unique Regulatory Mechanism of Sporulation and Enterotoxin Production in Clostridium perfringens - Ohtani, Kaori (American Society for Microbiology, 2013)
Clostridium perfringens causes gas gangrene and gastrointestinal (GI) diseases in humans. The most common cause of C. perfringens-associated food poisoning is the consumption of C. perfringens vegetative cells followed by sporulation and production of enterotoxin in the gut. Despite the importance of spore formation in C. perfringens pathogenesis, the details of the regulation of sporulation have not yet been defined fully. In this study, microarray and bioinformatic analyses identified a candidate gene (the RNA regulator virX) for the repression of genes encoding positive regulators (Spo0A and sigma factors) of C. perfringens sporulation. A virX mutant constructed in the food poisoning strain SM101 had a much higher sporulation efficiency than that of the wild type. The transcription of sigE, sigF, and sigK was strongly induced at 2.5 h of culture of the virX mutant. Moreover, the transcription of the enterotoxin gene was also strongly induced in the virX mutant. Western blotting confirmed that the levels of enterotoxin production were higher in the virX mutant than in the wild type. These observations indicated that the higher levels of sporulation and enterotoxin production in the virX mutant were specifically due to inactivation of the virX gene. Since virX homologues were not found in any Bacillus species but were present in other clostridial species, our findings identify further differences in the regulation of sporulation between Bacillus and certain Clostridium species. The virX RNA regulator plays a key role in the drastic shift in lifestyle of the anaerobic flesh eater C. perfringens between the vegetative state (for gas gangrene) and the sporulating state (for food poisoning).